1994
DOI: 10.1002/app.1994.070530109
|View full text |Cite
|
Sign up to set email alerts
|

Electrostriction of highly swollen polymer gel: Possible application for gel actuator

Abstract: A gel of poly(viny1 alcohol) highly swollen with dimethyl sulfoxide was demonstrated to actuate at a much faster rate (more than 1000 times) than those reported on conventional gel actuators in air and to flap a wing of 12.5 cm at a rate of 2 Hz with a span of 10 cm by periodically applying electric field. The action (8% in length) induced by the electric field reached several hundreds times larger than those reported on the conventional ferroelectric solid materials. The electrostrictive gel was, thus, found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 9 publications
1
44
0
Order By: Relevance
“…Hirai et al have first reported that dielectric gels made of poly (vinyl alcohol) swollen in dimethyl sulfoxide exhibit rapid contraction of 8 % within 0.1 s under an electric field of 250 V/mm [18]. Furthermore, plasticized poly(vinyl chloride) gels show amoebalike pseudopodial deformations and are applied to an electro-active artificial pupil.…”
Section: Dielectric Gels and Elastomersmentioning
confidence: 97%
“…Hirai et al have first reported that dielectric gels made of poly (vinyl alcohol) swollen in dimethyl sulfoxide exhibit rapid contraction of 8 % within 0.1 s under an electric field of 250 V/mm [18]. Furthermore, plasticized poly(vinyl chloride) gels show amoebalike pseudopodial deformations and are applied to an electro-active artificial pupil.…”
Section: Dielectric Gels and Elastomersmentioning
confidence: 97%
“…The bucky-gel actuator shows reversible bending more than 8,000 cycles at 30 Hz in air, which is associated with the electrophoretic polarization of ionic liquid in the active layer. Hirai first reported that dielectric gels made of PVA swollen in dimethyl sulfoxide exhibited rapid contraction of 8 % within 0.1 s under an electric field of 250 V/mm [62,72]. Furthermore, plasticized poly(vinyl chloride) (PVC) gels showed amoebalike pseudopodial deformations and applied to an electro-active artificial pupil.…”
Section: Electro-responsive Gelsmentioning
confidence: 99%
“…We assume that no charged species migrates inside the gel. Dielectric gels may be used as insulators, sensors and actuators (Finis and Claudi, 2007;Filipcsei et al, 2000;Hirai, 2007;Hirai et al, 1994;Hirai et al, 2000;Popovic et al, 2001;Zheng et al, 2000;Zrinyi et al, 2000). 0020-7683/$ -see front matter Ó 2008 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%